Specification for water cooling towers Part 2. Methods of test and acceptance testing (BSI, 1969)
Water coolers, Cooling towers, Coolers, Cooling equipment, Performance testing, Approval testing, Acceptance (approval), Testing conditions, Thermal measurement, Thermal testing, Test equipment, Temperature measurement, Flow measurement, Water, Acoustic measurement, Gas flow, Air, Wind loading, Numerical methods